Pengaruh Kecerdasan Emosional Komunikasi Dan Budaya Organisasi Terhadap Kinerja Karyawan Pada Perumda Air Minum Tirta Sanjiwani Kabupaten Gianyar - Cokorda Istri Agung Vera Nindia Putri; I Putu Agus Suwastawa; I Kadek Sara Mandiyasa; Tjokorda Gde Agung Wijaya Kesuma Suryawan; Komang Pande Indra Krisna Wiana (CV. Ulil Albab Corp, 2024)
The purpose of this study was to determine and analyze the effect of emotional intelligence, communication and organizational culture on employee performance at PERUMDA Tirta Sanjiwani Drinking Water, Gianyar Regency. This study uses census techniques so that all members of the population are involved as research subjects. Primary data collection was carried out using a questionnaire. The measurement scale uses a Likert Scale which consists of five answer choices. Hypothesis testing is done using multiple linear regression. Based on the results of the analysis, it can be concluded (1) Emotional intelligence, communication and organizational culture simultaneously have a positive and significant effect on employee performance, (2) Emotional intelligence has a positive and significant effect on employee performance, (3) Communication has a positive and significant effect on employee performance , and (4) Organizational culture has a positive and significant effect on employee performance. The implication of the results of this research is that improving employee performance can be done by motivating and encouraging employees to dare to take initiative.